2007
DOI: 10.3748/wjg.v13.i30.4136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional and psychological status in gastrointestinal cancer patients on tolerance of treatment

Abstract: AIM:To assess the effects of poor nutritional and psychological status on tolerance of cancer treatment and the recovery of physical performance status in patients with gastrointestinal cancer. METHODS:An epidemiological survey with respect to nutritional and psychological status in patients with gastrointestinal cancer was conducted among 182 operated patients in four provincial-level hospitals from December 2005 to June 2006. The food frequency survey method, state-trait anxiety inventory (STAI) and depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Coefficient alphas were reported to be 0.90 and 0.81 for the Chinese STAI-S and STAI-T, respectively15. Different cutoff values have been used to define anxiety in some studies16171819, but they were not applied in the present study due to the absence of sensitivity and specificity data in a Chinese population.…”
Section: Resultsmentioning
confidence: 92%
“…Coefficient alphas were reported to be 0.90 and 0.81 for the Chinese STAI-S and STAI-T, respectively15. Different cutoff values have been used to define anxiety in some studies16171819, but they were not applied in the present study due to the absence of sensitivity and specificity data in a Chinese population.…”
Section: Resultsmentioning
confidence: 92%
“…Some researchers have found that depression burden significantly influences severity of side effects of chemotherapy and burdens of fatigue [3,25]. Studies have shown that poor performance status leads to increased depression and negative coping with cancer [2,11,18].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is an important part of treatment for lung cancer patients. However, while on treatment, patients often experience great physical and mental distress 2,3 and poor performance status and quality of life (qol) 3 as a result of severe treatment-induced side effects.…”
Section: Introductionmentioning
confidence: 99%